Representation Of Cropping Culture Of The Benuaq Dayak Tribes In The Gantar Dance - Lolita, Carolina Meisye; Purwanti, Silviana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the representation of farming culture contained in the gantar dance based on semiotic analysis. This research uses a qualitative type of method with an interpretive method. Based on research, it is concluded that the representation of farming culture contained in the gantar dance based on semiotic analysis is knowledge, social and livelihood. The representation of knowledge is contained in the movement of holding/playing the kusak. Social representation is seen in the movements of holding the senak and stamping the foot and the kusak against the board, while the representation of farming is seen in the initial movements of forming a row, a straight pattern, and holding the senak.